Standardized Screening Protocol for NaCl Tolerance in Ricebean (Vigna umbellata) Genotypes at Early Seedling Stage under Controlled Environment - Nandeshwar, B. C.; De, D. K. (Innovations in Science and Technology Vol. 8, 2022)
The present study aimed to screen out available 30 Ricebean accessions in identified and standardize does of 120 mM of NaCl salt concentration for their salinity tolerance during early seedling stage to identify tolerant and susceptible genotypes. More salt reduces the growth and causes leaf damage, necrosis, and eventually subjected to death of the crop. Approximately, 21.5 million hectares of cultivatable land in Asia are affected due to salinity. Ricebean, belonging to family Fabaceae is a fast growing summer legume crop can produce high green fodder with high content of protein, calcium, phosphorous, tryptophan and also starch content. An experiment was set up in Completely Randomized Block Design (CRBD) along with three replications in a growth room of the Department of Plant Breeding, Faculty of Agriculture, Mohanpur, Nadia, West Bengal, India to study the potentiality of Ricebean to withstand against imposed salinity. Data were collected on different seedling growth parameters for screening of available 30 Ricebean genotypes at a 120 mM NaCl salinity level which was identified as standardize salt concentration for screening Ricebean genotypes after standardizing the protocol. Six genotypes viz., KRB-77 (81.58 and 0.41), KRB-273 (79.97 and 0.44) KRB-81 (79.63 and 0.44), KRB-10 (79.17 and 0.60), KRB-95 (76.48 and 0.51) and KRB-271 (71.31 and 0.54) were exhibiting more tolerance to imposed salinity level while genotypes viz., KRB-44 (19.48 and 1.73), KRB-66 (21.38 and 1.69), KRB-115 (22.25 and 1.26) KRB-56 (32.00 and 1.45) and KRB-211 (29.07 and 1.42) KRB-73 (33.10 and 1.43) were identified as susceptible to salinity, based on the study emphasized on germination percentage, relative reduction of dry weights, tolerance index (TI) and salinity susceptibility index (SSI) of different seedling traits.